Characterizing the 'Pseudo-Septum' in Fetal MRI: Diagnostic Implications for Septal Agenesis - Kataria, Bhavya (Medical Science: Trends and Innovations Vol. 5, 2025)
Background: Septal agenesis (SA), which involves the partial or complete absence of the septum pellucidum, is a rare congenital anomaly, with a prevalence of approximately 2-3 per 100,000 live births. This anomaly can occur in isolation or as part of complex congenital malformations such as septo-optic dysplasia (SOD), holoprosencephaly, or corpus callosum agenesis. SA and the "pseudo-septum" phenomenon are rare midline abnormalities identified in fetal MRI, often posing diagnostic challenges. Accurate differentiation between true SA and pseudo-septum is critical for prenatal counseling and management. This study aims to characterize the imaging features of true SA and pseudo-septum in fetal MRI and analyze their association with other central nervous system (CNS) anomalies and postnatal outcomes. Methods: A total of 79 fetuses with suspected midline anomalies underwent detailed MRI assessments at a tertiary care center in India. The presence of true SA and pseudo-septum was evaluated, along with associated findings like ventriculomegaly and corpus callosum agenesis. Diagnostic accuracy metrics for MRI were calculated using histopathological and clinical follow-up as gold standards. Statistical comparisons were performed to analyze associations between SA, pseudo-septum, and neurodevelopmental outcomes. Results: True SA was confirmed in 29 cases (36.7%), while 21 cases (26.6%) were identified as pseudo-septum. Ventriculomegaly was more frequent in pseudo-septum cases compared to true SA (66.7% vs. 31.0%, OR: 4.2, p=0.004). The sensitivity and specificity of MRI for diagnosing SA were 81.0% and 69.2%, respectively, with an overall accuracy of 77.2%. Postnatal outcomes showed a trend toward higher rates of neurodevelopmental delay in true SA cases (31.0% vs. 9.5%, p=0.051), although this did not reach statistical significance. Conclusion: This study highlights the diagnostic challenges posed by the pseudo-septum phenomenon in differentiating true SA. While fetal MRI remains a reliable tool, the presence of pseudo-septum and ventriculomegaly requires careful interpretation to avoid misdiagnosis. Enhanced imaging protocols and further research into the long-term outcomes of these conditions are essential to improve prenatal care and clinical management in resource-limited settings. Overall, these insights are essential for refining prenatal diagnostic strategies and improving the clinical management of fetal CNS anomalies.